Normative conceptions of romantic love among college students. [article]. - Tan, Allen L.
This study attempted to discover what a group of American college students considered the ideal love relationship. Sixty males and 60 females judged hypothetical romantic role pairs along 28 role differential scales. Data analyses showed that subjects expected married couples to display more absorption and dependence as well as warmth without idealization relative to unmarried couples; males also expected more sensitivity. Female subjects prescribed more sensitivity and warmth from men than men thought they should exhibit; males prescribed more absorption and dependence, and approach- avoidance from women. Women also seemed more concerned that their independence be respected. It was suggested that as American women assume more independence, they expect both sexes to display equal amounts of romantic behavior.